THE EFFECT OF PERSPECTIVE TAKING AND IMAGINED CONTACTS ON PERCEIVED SIMILARITY - Wirjawan, Armand; Takwin, Bagus (Faculty of Psychology, Universitas Diponegoro, 2022)
Several studies have shown that perspective taking may increase perceived similarity between two people via increased self-other overlap. However, there are reasons to doubt the efficacy of perspective taking, particularly due to the difficulty in leaving one’s own perspective to view the world from another’s. In two experiments, we tested the efficacy of perspective taking on increasing perceived similarity and, failing that, proposed a different method that may be more effective in increasing perceived similarity. The first study focused on perspective taking and was done with 95 participants (74% women) with a between-subjects design. The second study examined the effect of imagined contact with 59 participants (76% women) with a within-subjects design. The first experiment showed that perspective taking does not significantly affect perceived similarity, t(94) = -.10, p = .92, while imagined contact increases perceived similarity, t(58) = -2.54, p < .05. These experiments show that perspective taking does not improve perceived similarity, whereas imagined contact does increase perceived similarity. Practical implications are also discussed.